Low cost potato warehouse facility for Karnataka: a success story - Ali, S.; Kumar, B.B.; Kalleshwara Swamy, C.M.; Kadian, M.S.; Ramakrishna, B.V.; Singh, B.P. (2017)
Karnataka is one of the important potato growing states in peninsular India. Potato is mainly cultivated in Hassan, Belgaum, Chikkaballapur, Chickmagalur, Kolar, Bangalore Rural and Dharwad districts. It is grown as rain-fed kharif crop in Hassan, Belgaum, Chickmagalur and Dharwad districts and as rabi crop in Chickmagalur, Chikkaballapur, Kolar and Bangalore Rural districts under protective irrigation. Due to non-availability of quality planting material to Karnataka farmers, potato productivity is limited. Seed imported from North India (Punjab) is very expensive and incur about 50% of total production cost and small and marginal farmers cannot afford to procure quality seed every year as no certified seed is being produced locally. International Potato Center (CIP) has recommended an innovative low cost ware house facility as a model during 2014 and 2016 to retain farmers’ seed for subsequent planting seasons saving their seed input cost by 40%.